2020
DOI: 10.1111/nhs.12786
|View full text |Cite
|
Sign up to set email alerts
|

School nurses' perceptions regarding barriers and facilitators in caring for children with chronic diseases in school settings: A mixed studies review

Abstract: This study aimed to understand school nurses' perceptions regarding barriers to and facilitators for health care services for children with chronic diseases in school settings. Using the PubMed, Cumulative Index to Nursing and Allied Health Literature, Embase, and Web of Science databases, a mixed studies review was conducted for literature published between January 2011 and June 2020. We performed a mixedmethods systematic review using a convergent integrated approach. A quality appraisal of the included stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Prior work has identifed school-and parent-related barriers to optimal communication among caregivers, including school nurse availability, school district resources, and parent engagement [27,28]. Our fndings ofer other insights into what providers perceive to be systems-level factors which impact eforts to improve coordination of SBDC.…”
Section: Discussionmentioning
confidence: 92%
“…Prior work has identifed school-and parent-related barriers to optimal communication among caregivers, including school nurse availability, school district resources, and parent engagement [27,28]. Our fndings ofer other insights into what providers perceive to be systems-level factors which impact eforts to improve coordination of SBDC.…”
Section: Discussionmentioning
confidence: 92%
“…The model is widely used in psychology and healthcare studies. Uhm, Choi and Lee utilized the model effectively in two research papers regarding chronic diseases in young people [ 18 , 59 ]. It conceptualizes the idea that systems involving individuals’ environments play dimensional roles and frequently overlap.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this review was descriptive in nature (Stern, Jordan, & McArthur, 2014). Thus, the discussion meetings among the authors concluded using PICo (Population, phenomenon of interest, and the context) as a guide to formulate the review question and inclusion criteria (Lockwood, Munn, & Porritt, 2015;Stern, Jordan, & McArthur, 2014) as used in mixed studies reviews earlier (Uhm, Choi, & Lee, 2020;. Using PICo was facilitative since the review question does not require an intervention or a control group.…”
Section: Eligibility Criteria (Step 2)mentioning
confidence: 99%